2021
DOI: 10.1016/j.psj.2021.101289
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of pumpkin seed oil and sunflower oil along with vitamin E improves sperm characteristics and reproductive hormones in roosters

Abstract: This study evaluates the effects of pumpkin seed oil and sunflower oil along with vitamin E on the reproductive characteristics of aged roosters. Thirty Ross breeder roosters (45-wk-old) were assigned into 6 groups (5 birds/group) with the following diets: 1) control group (basal diet), 2) basal diet with 2% pumpkin seed oil as omega-3 fatty acid (PSO group), 3) basal diet with 2% sunflower oil as omega-6 fatty acid (SFO group), 4) basal diet with 200 mg/kg vitamin E (Control + vitE group), 5) basal diet and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…A Study concluded that PSO have antioxidant effect by down -regulation of gene expression Nrf2 that was increased after lead acetate exposure (57). PSO supplementation could inhibit lipid peroxidation through lowering level of MDA (59). Other studies proved that PSO is strong antioxidant as it elevated (GSH), (CAT) and decreased DNA fragmentation in testis (60 ,61) .…”
Section: Discussionmentioning
confidence: 90%
“…A Study concluded that PSO have antioxidant effect by down -regulation of gene expression Nrf2 that was increased after lead acetate exposure (57). PSO supplementation could inhibit lipid peroxidation through lowering level of MDA (59). Other studies proved that PSO is strong antioxidant as it elevated (GSH), (CAT) and decreased DNA fragmentation in testis (60 ,61) .…”
Section: Discussionmentioning
confidence: 90%
“…And the number of services was increased in response to Vitamin E treatment (Talib Ali, Bomboi, & Floris, 2016). The diets in roosters supplemented with Vitamin E increased sperm concentration, sperm viability, sperm motility and membrane integrity (Lotfi, Fakhraei, & Mansoori Yarahmadi, 2021). Dietary Vitamin E could increase sperm count, sperm motility, serum level of LH and FSH in aged male chicken (Amevor et al, 2022).…”
Section: Roles Of Vitamin E In Spermatogenesismentioning
confidence: 99%
“…However, the oil contains a lower amount of phytoestrogens than pumpkin seeds themselves (Andjelkovic et al., 2010; Pușcaș et al., 2020), but the oil is still considered useful for the treatment of hormone‐related disorders in men and women. Animal studies showed that PSO supplementation may improves sperm characteristics and reproductive hormones in roosters (Lotfi et al., 2021).…”
Section: Biological Activitymentioning
confidence: 99%